Apoptosis or autophagy, that is the question: Two ways for muscle sacrifice towards meat. Issue 2 (December 2015) - Lana, Alessandro; Zolla, Lello
Abstract: Background: Meat derives from muscle, but they are extremely different. The slaughtered muscle undergoes a number of biological changes during the maturation period, which is pivotal for the transformations that permit to obtain the final marketable product. Scope and approach: In this review a general process driving muscle-to-meat conversion is described, despite all the factors that can affect and diversify every individual process. We focus our attention on the switch from the normal, aerobic metabolism to the post-slaughter, anaerobic one, underlining all the consequences in terms of muscle reactions driving and influencing the transformation. The massive production of ROS is the pivotal event of the muscle-to-meat conversion, and muscle cells are stimulated to react as to cope with the oxidative stress. Despite the mobilization of defensive machineries, it soon becomes overwhelming and unsustainable: muscle cells are forced to die. Key findings and conclusions: ROS can induce both autophagy and apoptosis. Their role in muscle conversion is not completely clear, despite their differences have large influence on meat maturation and final product. A deeper understanding is pivotal on this argument as to better manage meat production. Highlights: Slaughtered muscle undergoes aerobiosis/anaerobiosis switch. Oxidative stress induces muscle defensive reaction. Apoptosis and autophagy are induced by ROS, so they are possible in muscle cells. Cellular rescue attempts fail; muscle cells are forced to die. With the exact knowledge of underlying mechanisms, meat management can be improved.